2019
DOI: 10.37080/nmj.61
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality among College Students in Kathmandu Valley, Nepal

Abstract: Introduction: Many college students suffer from sleep disorders, including insomnia, and sleep deprivation, resulting in a poor sleep quality. Students are at risk for sleep disorders, and those at risk may also be at risk for academic failure. The main aim of the study is to assess the level of sleep quality among college students in Kathmandu, Nepal. Methods: A cross-sectional study was conducted with 504 students of class 11 and 12 of any faculties among selected colleges o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…[18] Another study conducted in Kathmandu Valley Nepal among 504 college students showed contrasted finding that 59.1% of the respondents had poor quality of sleep. [19] This present study findings regarding the duration of sleep showed that 68.8% of the respondents had seven hours or more sleep whereas 31.2% had less than seven hours of sleep. A cross sectional study conducted in Kathmandu valley, Nepal among 504 college students showed the similar findings that 34.9% of the respondents had reported less than seven hours of sleep.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…[18] Another study conducted in Kathmandu Valley Nepal among 504 college students showed contrasted finding that 59.1% of the respondents had poor quality of sleep. [19] This present study findings regarding the duration of sleep showed that 68.8% of the respondents had seven hours or more sleep whereas 31.2% had less than seven hours of sleep. A cross sectional study conducted in Kathmandu valley, Nepal among 504 college students showed the similar findings that 34.9% of the respondents had reported less than seven hours of sleep.…”
Section: Discussionsupporting
confidence: 45%
“…[16] Another study conducted among 504 students in Kathmandu Valley revealed there was slightly difference between male and female respondents i.e., 55.21% of males and 65.78% of females had poor sleep quality. [19] This study may have some limitations. Firstly, the sample size was small and from the same institute which may decrease the generalizability of the findings to the other settings.…”
Section: Discussionmentioning
confidence: 92%
“…A study on Nepalese college students has shown the poor quality of sleep among the majority of them. 21 Higher prevalence of poor sleep quality among medical students as compared to other non-medical students and the general population has also been reported and several factors including medical students’ attitudes, knowledge of sleep, and academic demands have been identified as the causative factors. 22 …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly. it seems that poor sleep of medical students depends on the country: 40.60% of Iranian students reported poor sleep quality [24] while 69% of Lithuanian medical students reported good to excellent nocturnal sleep [25]; 70% of Honk Kong students of medicine reported sleep deprivation [26], 47.1% of medical students in India reported refreshing sleep [27], and 31.5% of medical students suffered from sleep deprivation according to a study conducted in Nepal [28]. Physical activity of university students has been largely investigated in scientific literature [3,5,6,17,22,23,29] also comparing different geographical provenience [22].…”
Section: Introductionmentioning
confidence: 99%